2013
DOI: 10.1007/jhep08(2013)095
|View full text |Cite
|
Sign up to set email alerts
|

Stability of vacua in new massive gravity in different gauges

Abstract: We consider AdS3 and warped AdS3 vacua in new massive gravity and study the highest weight modes and general propagating modes as a set of solutions for the linearized equations of motion. We observed that depending on the choice of gauge there are two types of solutions. We show that for warped AdS3 vacuum, the massless modes which appear only in the harmonic gauge have zero energy density and do not get higher curvature corrections. By computing the energy density it can be shown that all massive modes have … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…and energy is positive for both branches. The above charge construction for the quadratic curvature gravity is widely used in the literature; for example, see [23,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69]. Now, let us generalize the charge construction for the quadratic curvature gravity to the higher curvature gravity with the Lagrangian density constructed from the Riemann tensor and its contractions.…”
Section: Charges Of Quadratic Curvature Gravitymentioning
confidence: 99%
“…and energy is positive for both branches. The above charge construction for the quadratic curvature gravity is widely used in the literature; for example, see [23,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69]. Now, let us generalize the charge construction for the quadratic curvature gravity to the higher curvature gravity with the Lagrangian density constructed from the Riemann tensor and its contractions.…”
Section: Charges Of Quadratic Curvature Gravitymentioning
confidence: 99%
“…The stability of these solutions in massive gravity models have been studied in various cases. For example, in NMG theory it was shown that the warped AdS geometry is unstable in all range of parameters [36] while in four dimensional gravity theories instability of Schwarzschild black holes and Kerr geometries have been studied in [37,38]. Therefore this kind of instability may have the same origin and investigating this point could help us to understand the physics of massive spin-2 excitations.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…It is easy to see that M > 1 leads to stable frequencies. There is an important point regarding the solutions (35) and (36). As mentioned in [9], these two modes are not orthogonal, so they can not be interpreted as independent massive modes in the theory and they might be some missing solutions to the linearized eq.…”
Section: Analytical Analysis Of Qnm'smentioning
confidence: 99%
“…On the other hand, the classical (in) stability condition of the BTZ black hole was recently determined by the condition of M 2 > 0(< 0) regardless of the horizon size r + [34] (see also [35] for stability issue in NMG). The case of M 2 = 0 corresponds to the critical gravity where all thermodynamical quantities are zero and logarithmic modes appear.…”
Section: Jhep04(2014)058mentioning
confidence: 99%